2016
DOI: 10.1038/ctg.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Intestine eQTLs from an Anti-TNF-Resistant Crohn's Disease Cohort Inform IBD Genetic Association Loci

Abstract: OBJECTIVES:Genome-wide association studies (GWAS) have identified loci reproducibly associated with inflammatory bowel disease (IBD) and other immune-mediated diseases; however, the molecular mechanisms underlying most of genetic susceptibility remain undefined. Expressional quantitative trait loci (eQTL) of disease-relevant tissue can be employed in order to elucidate the genes and pathways affected by disease-specific genetic variance.METHODS:In this study, we derived eQTLs for human whole blood and intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 80 publications
8
33
0
Order By: Relevance
“…The other locus of IKZF3 was also reported to be associated with autoimmune diseases. Rs12946510 was reported to be an expressional quantitative trait loci (eQTL) of IKZF3 , which increased the susceptibility with inflammatory bowel diseases [28]. Future studies using gene sequencing analysis could provided further evidences of IKZF3 .…”
Section: Discussionmentioning
confidence: 99%
“…The other locus of IKZF3 was also reported to be associated with autoimmune diseases. Rs12946510 was reported to be an expressional quantitative trait loci (eQTL) of IKZF3 , which increased the susceptibility with inflammatory bowel diseases [28]. Future studies using gene sequencing analysis could provided further evidences of IKZF3 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our finding, a recent study reported significant RNASET2 eQTL in whole blood from patients resistant to anti-TNF therapy. 41 Moreover, RNASET2 disease-associated SNPs correlated with therapeutic failure of anti-TNF therapy, and intestinal resection of >40 cm clinical characteristic of overall disease severity. 31 In patients with a history of multiple resections, RNASET2 disease-risk SNP was associated with a shorter time to repeat surgery in CD.…”
Section: Discussionmentioning
confidence: 99%
“…We checked for the presence of known CD or UC associated genes in the networks, using data from two studies of single nucleotide polymorphisms (SNPs) 67,68 and one study of CD expression quantitative trait loci (eQTLs). 69 Using hypergeometric significance tests, we found that the PCeE network was significantly enriched in all tested lists: genes with UC…”
Section: Evaluating the Disease Relevance Of The Subnetwork Specific mentioning
confidence: 97%